The recruiting and hiring of older workers - LIEVENS, Filip (Institutional Knowledge at Singapore Management University, 2012)
Abstract This chapter reviews five key components,of the recruitment process with regard to an aging workforce. First, targeted recruitment entails that organizations understand the needs, preferences, and strengths of older workers. Second, the recruitment message should communicate job and organizational characteristics that are attractive to older jobseekers. Third, the recruitment source should be consistent with the media useand job search behaviors of older jobseekers. Fourth, the characteristics and behaviors of recruiters play an essential role in the recruitment of older applicants. Finally, organizations need to convey an attractive image of themselves as employers for older workers. Throughout the chapter, best practices are contrasted with available research evidence, and directions for future research are outlined.